Implementasi Pembelajaran Fisika Berbantuan Phet Simulation Untuk Meningkatkan Hasil Belajar Peserta Didik Materi Fluida Statis - Qoidatun Nisak (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2023)
This research is motivated by the non-optimal achievement of student learning outcomes. This study aims to determine the effect of phet simulation learning media with problem-based learning (PBL). This type of research uses classroom action research methods with 2 cycles, data collection techniques with observation, interviews, tests and documentation.Data analysis techniques use descriptive model analysis starting from data collection, data reduction and data presentation. This research was carried out on static fluid material physics learning which was carried out in class XI-5 and XI-6 SMA Negeri 1 Menganti. Based on the research that took place in 2 (two) cycles, it was found that changes in learning outcomes varied. In the first cycle of class XI - 5 the learning outcomes achieved were 91.87% of the classical completeness score with an average achievement of 78.81, then in the first cycle of class XI - 6 the learning outcomes achieved were 86.11% of the classical completeness value with an average achievement 81.81 while in cycle II the learning outcomes achieved in class XI - 5 were 100% of the classical completeness score with an average achievement of 86.17. in cycle II the learning outcomes achieved in class XI – 6 were 100% classical completeness score with an average achievement of 86.17, the percentage of positive responses of students carrying out learning with phet simulation was 92.96%, while the negative response was 7, 04%, From these results it can be concluded that the use of phet simulation learning media on static fluid material.